Linkages of Mother’s Status and Autonomy in the Household With Childhood Stunting in Indonesia - Yuhan, Risni Julaeni; Kutanegara, Pande Made; Budiani, Sri Rahayu (Journal of Population and Social Studies [JPSS], 2024)
Maternal status and autonomy play a crucial role in achieving gender equality, which in turn has the potential to decrease the incidence of stunting, a persisting challenge in Indonesia. This study explores the correlation between stunting and factors such as maternal status and autonomy at the provincial level across Indonesia. It employs methodologies like cross-tabulation and odds ratio, complemented by the Mantel-Haenszel test for analytical purposes. The research utilizes data from the 2017 Indonesia Demographic and Health Survey (IDHS), the Indonesian Nutrition Status Survey (SSGI) of 2022, and publications by the Central Statistics Agency from 2021 and 2022. Findings indicate a notable correlation between the prevalence of stunting and women’s participation in decision-making, particularly regarding physical mobility and the Net Enrollment Rate (NER) for junior high school females. To address this discovery, there is a pressing need for governmental and other relevant entities to focus on enhancing educational attainment and ensuring that all initiatives are grounded in principles of gender equality.